Interdisciplinary communication and collaboration as key to improved nutritional care of malnourished older adults across health‐care settings – A qualitative study. (11th June 2020) - Verwijs, Marije H.; Puijk‐Hekman, Saskia; van der Heijden, Ellen; Vasse, Emmelyne; de Groot, Lisette C. P. G. M.; de van der Schueren, Marian A. E.
Abstract: Background: Malnutrition is a risk factor for impaired functionality and independence. For optimal treatment of malnourished older adults (OA), close collaboration and communication between all stakeholders involved (OA, their caregivers and health‐care and welfare professionals) is important. This qualitative study assesses current collaboration and communication in nutritional care over the continuum of health‐care settings and provides recommendations for improvement. Methods: Eleven structured focus group interviews and five individual interviews took place in three regions across the Netherlands from November 2017 until February 2018, including OA, caregivers and health‐care and welfare professionals. Various aspects of collaboration and communication between all stakeholders were discussed. Interviews were transcribed and analysed using a thematic approach. Results: Six main themes emerged: causes of malnutrition, knowledge and awareness, recognition and diagnosis of malnutrition, communication, accountability and food preparation and supply. Physical and social aspects were recognized as important risk factors for malnutrition. Knowledge and awareness regarding malnutrition were acknowledged as being insufficient among all involved. This may impair timely recognition and diagnosis. Responsibility for nutritional care and its communication to other disciplines are low. Food preparation and supply in hospitals, rehabilitation centres and home care are below expected standards. Conclusion: Many stakeholders are involved in nutritional care of OA, and lack of communication and collaboration hinders continuity of nutritional care over health‐care settings. Lack of knowledge is an important risk factor. Establishing one coordinator of nutritional care is suggested to improve collaboration and communication across health‐care settings.